Effect of Supplementation of Ammonium Sulphate and Sulphur Coated Urea on Nutrient Digestibility, Blood parameters and Milk Production in Crossbred Cows - Rahal, Anshu (Indian Journal of Animal Nutrition, 2018)
Fifteen lactating crossbred cows were divided into 3 groups of 5 animals each to see the effect of supplementation of ammonium sulphate or sulphur coated urea on feed intake, nutrient digestibility, blood parameters and milk production for 3 months. The animals in Group 1 were fed as per requirements (NRC, 2001) while the animals in group II and III were supplemented with 30 g ammonium sulphate or 30 g sulphur coated urea in concentrate mixture in two doses (15 g each) at the time of milking. There were no significant differences among the groups with regards to DM or TDN intake. The digestibility of EE, CF, NFE, NDF and ADF was found to be similar in the three groups except that CP digestibility was higher in supplemented groups. The levels of serum glucose urea concentration were similar in all the groups while those of total protein and total albumin were higher (P